2011
DOI: 10.1302/0301-620x.93b8.25940
|View full text |Cite
|
Sign up to set email alerts
|

Distal tibial fracture repair in a neurofibromatosis type 1-deficient mouse treated with recombinant bone morphogenetic protein and a bisphosphonate

Abstract: Congenital pseudarthrosis of the tibia is an uncommon manifestation of neurofibromatosis type 1 (NF1), but one that remains difficult to treat due to anabolic deficiency and catabolic excess. Bone grafting and more recently recombinant human bone morphogenetic proteins (rhBMPs) have been identified as pro-anabolic stimuli with the potential to improve the outcome after surgery. As an additional pharmaceutical intervention, we describe the combined use of rhBMP-2 and the bisphosphonate zoledronic acid in a mous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
29
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 37 publications
4
29
1
Order By: Relevance
“…We observed a gain in the number of osteoclasts at the Nf1-null murine fracture site, in agreement with previous studies (51)(52)(53)(54)(55)(56)(57). In vitro studies have shown a biphasic effect of b-catenin on osteoclast proliferation and differentiation (58).…”
Section: Discussionsupporting
confidence: 92%
“…We observed a gain in the number of osteoclasts at the Nf1-null murine fracture site, in agreement with previous studies (51)(52)(53)(54)(55)(56)(57). In vitro studies have shown a biphasic effect of b-catenin on osteoclast proliferation and differentiation (58).…”
Section: Discussionsupporting
confidence: 92%
“…Bone morphogenic proteins (BMPs) are known for their ability to promote osteoprogenitor differentiation 39 but had limited effect on the differentiation of Nf1 +/− osteoprogenitors and on bone union in Nf1 +/− mice 40,41 . Recombinant hBMP2 (100 ng.ml −1 ) was unable to stimulate ALP activity, nor the formation of CFU–Ob in BMSC cultures from Col2-Nf1 KO mice, although it did, as expected, promote CFU–Ob formation and ALP activity in WT BMSC cultures, following 2 weeks of treatment (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Some experimental in vitro and in vivo research showed a great potential of using BPs in healing of fractured bones, reducing osteoarthritis, or enhancing ingrowth of bone allografts (5,25,27). It was earlier proposed that the introduction of bisphosphonate compounds can be a very promising procedure connected with the treatment of musculoskeletal disorders in clinical practice (19,27,28). Furthermore, the data obtained in the present study demonstrates that the use of pamidronate as a cocomponent of cement also has some positive effect on muscle homeostasis in rats after the surgery.…”
Section: Resultsmentioning
confidence: 99%